Newspapers and Human Rights Violations in North-East Nigeria: an Agenda-Setting Perspective - Ayih, Livinus Jesse (International Journal of Education, Culture, and Society, 2025)
This study examines how newspapers shape public attention to human rights issues in Northeast Nigeria through their agenda-setting function. The research objective is to assess the capacity of newspapers to foreground human rights concerns and the factors that constrain this role. Anchored in agenda-setting theory, the study employs a review of extant literature. Key findings indicate that newspapers can amplify marginalized voices by consistently highlighting their struggles and, through advocacy and investigative reporting, raise awareness and stimulate public discussion of critical human rights issues. However, effectiveness is limited by political bias that fosters selective reporting, commercial pressures that privilege profit over social responsibility, and media ownership influences that skew the framing of human rights stories, jointly impeding objective and comprehensive coverage. The study concludes that, despite these constraints, newspapers remain crucial in the digital media era for promoting accountability, transparency, and social justice. The contribution and implication are that strengthening editorial independence and ethical standards within newspaper organizations can enhance agenda-setting on human rights and sustain their role in holding power to account.